Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. The Impact of Psychological Factors on the Purchasing Desire Among Members of the Saudi Society In the period between 2021 - 2023 ADMr. Bandar Abdul-Rahim Al-Ghamdi2. The extent to which Palestinian audit offices comply with the requirements of the International Standard for Quality Management (ISQM 1)Ms. Etedal Robeen Siaj3. The impact of administrative creativity in consolidating organizational culture in private schools  in the Holy CapitalMs. Ghaliah Habibullah Turkstany4. The impact of the audit committee on the disclosure of intellectual capitalAn applied study in Sudanese industrial companiesMr. Sabi Mahmood Abdullah, Co-Prof. Mohamed Elnair Mohamed Elnour5. The Role of Human Resources Strategy in Achieving Professional Growth  in Private Universities Considering Vision 2030Asst-Prof. Salma Mohammed Jaghoubi, Ms. Sarah Abdullah Owayyid6. Strategic analysis of human resources management in its work to enhance organizational performance in the telecommunications sector, Kingdom of Saudi ArabiaDr. Sadiq Ali Al-Shuwaikhat, Dr. Haya Ibrahim Al Tuwaym, Dr. Sara Saad Al-Dawsari7. Employees Empowerment and its Relationship to Competitive AdvantageA Case Study / Hotel Sector / Sultanate of OmanMr. Khalaf Sulaiman Albahri8. Commitment to conformity in the international sales contractDr. Muneer Ali Hulaiel
Keywords: Journal of Economic, Administrative and Legal Sciences